Microbial changes in soil during a maize crop season in no-till and conventional systems - Vargas, Luciano Kayser; Selbach, Pedro Alberto; Sá, Enílson Luiz Saccol de (Pesquisa Agropecuaria Brasileira, 2004)
The availability of black oat residues, with high C:N ratio, leads to microbial immobilization of soil nitrogen, demanding special strategies to supply nitrogen to subsequent crops. The objective of this work was to evaluate shifts in microbial community structure due to the availability of black oat residues and nitrogen applications during the corn growing season. Soil (Paleudult) samples were collected on the day of the corn seeding and after 46, 62, 88 and 112 days. Nitrogen fertilizer was applied 25 and 49 days after corn seeding. Changes in microbial community were assessed by microbial biomass carbon (C) and nitrogen (N), ninhydrin-reactive N (N-Nin) and carbohydrates (CHO) ratios, besides the analysis of the rDNA of bacteria and fungi. Changes in microbial community shown by rDNA analysis were more related to C:N and C:N-Nin ratios than to C:CHO ratio. The C:N and C:N-Nin ratios and the analysis of the rDNA showed that microbial community was predominantly fungal at the beginning of the evaluation period. After nitrogen application, the bacterial population became preponderant and, at the end of the evaluation period, microbial community turned back to a composition similar to the initial.